2021
DOI: 10.2147/rmhp.s317852
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β-Thalassemia and Other Hemoglobinopathies in Bangladeshi University Students and Ready-Made Garment Workers

Abstract: Background The inheritable thalassemia and other structural hemoglobinopathies are prevalent globally. In Bangladesh, there is a scarcity of studies concerning thalassemia and other structural hemoglobinopathies. Hence, the present study investigated the prevalence and distribution of β-thalassemia and other hemoglobinopathies among the university students and ready-made garment (RMG) workers. Methods A cross-sectional study was conducted, whereas a total of 989 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Surprisingly, 759 (45.3%) knew the disease could not be transmitted through blood transfusion. This is close to the outcome of a study conducted by Islam et al (2021) where 32.1% responded the same.…”
Section: Resultssupporting
confidence: 85%
“…Surprisingly, 759 (45.3%) knew the disease could not be transmitted through blood transfusion. This is close to the outcome of a study conducted by Islam et al (2021) where 32.1% responded the same.…”
Section: Resultssupporting
confidence: 85%
“…Twelve studies reported data on the prevalence of beta‐thalassemia in Asia from non–population‐based, selected samples of subjects 25,52,53,55–63 . The prevalence of beta‐thalassemia intermedia was described in a number of studies by retrospectively determining phenotype (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…51 Twelve studies reported data on the prevalence of betathalassemia in Asia from non-population-based, selected samples of subjects. 25,52,53,[55][56][57][58][59][60][61][62][63] The prevalence of beta-thalassemia intermedia was described in a number of studies by retrospectively determining phenotype (Table S7). Prevalence ranged from 14 per 100 000 pregnant women and husbands from the Guangdong province in China in 2012 53 to 615 per 100 000 individuals from northern India and Nepal in 2008.…”
Section: Prevalence Of Alpha-and Beta-thalassemia Reported In Non-pop...mentioning
confidence: 99%
“…The lower body mass index for β-thalassemia patients typically experiences growth retardation and decreased muscle mass may be responsible for the significant decrease in the mean serum creatinine level. According to the results of recent studies, the main prospective causes of morbidity and mortality in β-thalassemia patients were liver disease, cardiac disorders, diabetes, infection, and cancer due to long-term complications [20,21]. Due to socioeconomic inequities in our nation, the majority of β-thalassemia patients do not receive iron chelating therapy regularly.…”
Section: Discussionmentioning
confidence: 99%